Sound quality inside small meeting rooms with different room shape and fine structures. (June 2015) - Zhao, Sipei; Qiu, Xiaojun; Cheng, Eva; Burnett, Ian; Williams, Nick; Burry, Jane; Burry, Mark
Abstract: This note is intended to understand relative importance of room shape and fine structures on the sound quality inside small meeting rooms in terms of the reverberation time, the sound field distribution and the speech transmission index with similar room volume, surface area and the absorption coefficients. First, different shaped rooms with smooth walls are modeled and simulated to investigate the effects of room shape on the sound quality, and then hyperboloid cells are made on the walls to examine the influence of fine structural surface on sound quality with both regular and random arrangements. It is found that the reverberation time is affected significantly by the room shape while is not sensitive to the hyperboloid cells. The sound field distribution is affected little by the room shape and the hyperboloid cells and the difference is smaller than the Just-Noticeable-Difference in most cases. The impact of the room shape and fine structural surface on the speech transmission index mainly lies in the transition area between the direct sound and the reverberant sound. The reliability of the simulation remarks is confirmed by the experiments carried out in two different meeting rooms. The main conclusion of the note is that when the room volume, the surface area and the absorption coefficients are kept constant, the room shape and fine structural surface have little impact on the sound field distribution and speech intelligibility inside small rooms with ordinary surface absorption, while the reverberation time is affected significantly by room shape but slightly by the fine structural surface.